Note from the editor: Back to development in the XXI century - Mariana Heredia (economic sociology. perspectives and conversations, 2024)
Outside the major Western nations, the word "development" is often used as a substitute or synonym for progress. Both project into the future and celebrate science and technology as an outpost of civilization, both are confident of a destiny of ever-increasing improvements for humankind. As documented by Gilbert Rist (1997), the shift in the usage of one word to the other occurred at the end of World War II and was not anodyne.
Keywords: 300